Kohabitasi Dalam Perspektif H.R. Al-Tirmidzi Dan Pasal 412 Ayat (1) KUHP - Hasna Hamidah; Tajul Arifin (Pusat Riset dan Inovasi Nasional, 2024)
This study analyzes the HR perspective. At-Tirmidhi regarding cohabitation in the context of Article 412 paragraph (1) of the Criminal Code in Indonesia. By using a qualitative approach, this research highlights the Islamic perspective on relationships between men and women outside of marriage and its relevance to positive law. The research results show the importance of maintaining moral norms in relationships, but there are differences between Islamic law and positive law in enforcing living together. This study provides insight into religious perspectives on social phenomena and their impact on law and social policy. This also provides a basis for understanding the dynamic relationship between religious values and positive law in dealing with social problems.